Process and optimization of palm-oil based water-in-oil-in-water (W/O/W) multiple nanoemulsion encapsulating tocotrienols and caffeic acid with cisplatin as a synergistic anticancer treatment - Raviadaran, Revathi (2021)
Water-in-oil-in-water (W/O/W) multiple emulsion consist of oil globules containing small internal water droplets dispersed in an external continuous water phase. They possess the potential to encapsulate active compounds such as drugs, nutrients and flavonoids to protect them from degradation by external stresses such as pH, light, temperature, oxygen and gastrointestinal conditions during the transit. Despite their potential for sustained release, multiple emulsion is not widely used due to their thermodynamic instability culminating in phase separation. With rising fatality due to cancer, as well as the tumour resistance and severe side effects of the most commonly used chemotherapeutic drug, cisplatin-cis-diamminedichloroplatinum (CIS), it is essential to explore a combined therapy of using CIS with natural chemopreventive active compounds. Through this, the toxic dosage of CIS could be reduced and synergistic effects could be achieved. This study aims to formulate stable natural tocotrienol rich fraction (TRF) and caffeic acid (CA) encapsulated in palm oil-based W/O/W multiple nanoemulsion and evaluate its anticancer and toxicity effects towards cancer and normal cell lines, respectively. This was achieved through multi-faceted experimentations which commenced with the formulation of stable water-in-palm oil (W/O) nanoemulsion using ultrasonicator and microfluidizer emphasizing on the interaction between the oil and emulsifier to form rigid oil-water interface. For this, the effects of the addition of polyglycerol polyricinoleate (PGPR), medium-chain triglyceride (MCT), lecithin and sodium chloride (NaCl) towards the stability of nanoemulsion were mainly evaluated. Following this, stable W/O/W multiple nanoemulsion encapsulating TRF and CA was formulated using ultrasonicator and microfluidizer, as well as focused on the energy consumption and oxidation of palm oil in the processed emulsion. The effects of Sucragel (oil-soluble thickener) for the oil phase and Xanthan gum (water-soluble thickener) for the internal water phase, as well as tonicity such as hypotonic, isotonic and hypertonic towards the stability of multiple nanoemulsion, were evaluated. Finally, the anticancer and toxicity effects of TRF and CA encapsulated W/O/W multiple nanoemulsion with CIS towards cancer (A549 and HEP G2) and normal (HEK 293) cell lines were examined. Stable palm oil-based W/O nanoemulsion was produced using 61.25 wt% of palm oil, 26.25 wt% of MCT, 2.5 wt% of PGPR and 10.0 wt% of water. The W/O nanoemulsion was formed under optimized ultrasonicator conditions of 40% amplitude, 180 s of irradiation time, while for microfluidizer it was 350 bar and six cycles. The obtained mean droplet diameter (MDD) and dispersity index (DI) of W/O nanoemulsion were 143.1±8.8 nm and 0.131±0.094, respectively, with no sedimentation observed for 2 weeks. PGPR’s polyricinoleate non-polar fatty acids were found to bound to palm oil’s non-polar fatty acids through van der Waals intermolecular forces. At the same time, it’s polyglycerol polar head interacted with water molecules through hydrogen bonding and bound to glyceride units of palm oil that strengthened its interaction at the interface. The addition of NaCl further reduced MDD by 70 nm and improved the stability of nanoemulsion through electrostatic repulsions attributed to the dissociation of Na+ and Cl- ions. Then, W/O/W multiple nanoemulsion was formed under optimized ultrasonicator conditions of 40% amplitude, 180 s of irradiation time, while for microfluidizer it was 350 bar and eight cycles. This is the first work that successfully utilized Sucragel (oil-based thickener) in imparting enhanced stability in W/O/W multiple nanoemulsion. Through this, the thickened oil phase retained and protected the internal water droplets by forming a packed and stable network in the oil globules and rigid stability at the oil-water interface. W/O/W multiple nanoemulsion with isotonic stabilization gave the lowest change in MDD, concentration of NaCl and water content by 1.34%, 2.97% and 0.40%, respectively, due to the reduced movement of water. The optimized W/O/W multiple nanoemulsion consist of 10.0 wt% of W/O nanoemulsion, 89.0 wt% of water and 1.0 wt% of Tween 80. The W/O nanoemulsion consist of 10.0 wt% of water, 1.0 wt% of Sucragel, 2.5 wt% PGPR and 86.5 wt% of palm oil (70:30 of palm oil:palm MCT oil). It possessed 175.5±9.8 nm and 0.232±0.012 of MDD and DI, respectively. After 180 days of storage for the TRF and CA encapsulated W/O/W multiple nanoemulsion, <4% change in water content, conductivity, NaCl concentration, as well as the concentration of TRF and CA were measured. ~99% and ~98% encapsulation efficiencies of TRF and CA, respectively, were obtained. Higher TRF and CA concentrations in the range of 100.0% - 237.5% were required to achieve inhibitory concentration (IC 50) for A549 and HEP G2 in solution as compared to nanoemulsion. TRF, CA and CIS synergistically improved apoptosis in the late apoptotic phase in A549 and HEP G2 by 23.1% and 24.9%, respectively. The generation of reactive oxygen species was enhanced using TRF:CA:CIS by 16.9% and 30.2% for A549 and HEP G2, respectively. Cell cycle analysis showed enhanced cell arrest in the G0/G1 phase for both A549 and HEP G2. TRF, CA and CIS led to cell death in A549 and HEP G2. For HEK 293, ~33% cell viability was found when only CIS was used, while ~95% cell viability was observed when TRF, CA and CIS were used. These outcomes distinctly show that stable TRF and CA encapsulated W/O/W multiple nanoemulsion was successfully formulated, which synergistically treated cancer cell lines, as well as increased the viability of normal cell line due to reduced toxicity. These are especially true for the cancer and normal cell lines evaluated in this study. Overall, this work contributed to the advancement of knowledge and application of palm oil-based W/O/W multiple nanoemulsion encapsulating natural active compounds to be used synergistically with chemotherapeutic drug for more effective and less toxic cancer treatment.